PERBEDAAN LAMA PELEPASAN TALI PUSAT ANTARA PERAWATAN TERBUKA DAN TERTUTUP PADA BAYI BARU LAHIR DI BIDAN PRAKTIK MANDIRI LISMARINI PALEMBANG TAHUN 2015 - Tiara Fatrin; Bela Vista (STIKES Abdurrahman. Pusat Informasi dan Manajemen, 2016)
The treatment of umbilical cord is nursing actions aimed at caring for the umbilical cord in the newborn. The correct and proper umbilical cord care determines the long or not the umbilical cord loss because in addition to the loss of the umbilical cord can speed it can also reduce the risk of infection, reducing infant mortality. The research aimed to know the difference time of the umbilical cord loss between opened and closed umbilical cord care. Techniques used in sampling that was generally non random,